KINERJA DAN STRATEGI PENGEMBANGAN PRIMKOPTI KABUPATEN PESAWARAN PROVINSI LAMPUNG - Rini Mega Putri; Dyah Aring Hepiana Lestari; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze cooperative performance as business entities, cooperative’s contribution towards development, the non economic advantage of cooperative (satisfied) for members, and development strategy of cooperative.  This research was taken at Primkopti in Pesawaran District, Lampung Province which has been chosen purposively.  Data of this research was collected in Desember 2016.  This research uses a case study method.  Total respondents were 54 members of cooperative to answer the third destination. Respondents were taken by simple random sampling method.  The data analysis method used was quantitave descriptive analysis, contribution analysis toward development, customer satisfaction index analysis and SWOT analysis.  The results of this research showed that business entities performance of Primkopti included into less qualified category.  Primkopti has less contributed towards the development of Pesawaran District.  Primkopti’s members satisfaction levels was 70,57 percent, it meant that the members of Primkopti felt satisfied by the performance of the services provided by Primkopti.  Tthe priority strategic of Primkopti are using Primkopti’s financial and capital to collaboration with soybean suppliers, optimizes high community demand of Primkopti’s product (soybean breaker) to increase revenue and resolve soybean’s continuous distribution, using the cheap soybean breaker product prices to dominating the market and competing with competitors. Key words : Primkopti, SWOT analysis, tripartite approach